Occupational Safety and Health in Ecuador: Legal Frameworks, Labor Inspectorate Challenges and Insights - Ruiz Salvador, Lourdes; Alvarez Llerena, Mariuxi; Alvarez Llerena, Carlos; Gupi, Marsidi (International Journal of Occupational Safety and Health, 2025)
This study examines the legal framework of Occupational Safety and Health (OSH) in Ecuador, focusing on labor inspection in the province of Cañar. With a qualitative approach, the research employed inductive, analytical, synthetic, and dogmatic methods, utilizing bibliographic review and documentary analysis. It was identified that the lack of adequate inspections is due to the shortage of labor inspectors and the omission of key requirements in evaluations. As a result, workers are exposed to occupational risks without adequate supervision. The study concludes that it is urgent to strengthen the labor inspection system by increasing the number of inspectors, standardizing procedures, and imposing stricter sanctions. These measures would help ensure compliance with OSH regulations and the effective protection of workers.